Impact of liver disease severity on postoperative pain after living donor liver transplantation: a prospective observational study - Priyanka Chuttani; Gaurav Sindwani; Viniyendra Pamecha; Nihar Mohapatra; Mahesh Kumar Arora (Clinical Transplantation and Research)
Background : Managing pain after liver transplantation presents unique challenges. The severity of this pain may correspond to elevated endogenous opioid peptide levels, which in turn depend on the severity of liver disease, as represented by the Model for End-Stage Liver Disease (MELD) score. Hence, this study aimed to assess the difference in fentanyl consumption after liver transplantation between patients with high and low MELD scores. Methods : Patients meeting the inclusion criteria and scheduled for living donor liver transplantation were prospectively recruited. A standard anesthesia protocol was followed for intraoperative management. Postoperatively, intravenous patient-controlled analgesia was initiated. Visual analogue scores, fentanyl consumption, sedation levels, and complications such as pruritus, nausea, and vomiting were recorded. Results : A total of 40 patients were included. The patients were divided into low-MELD (<25) and high-MELD (≥25) groups, with 20 patients in each. Fentanyl consumption was significantly higher in the low-MELD group on both postoperative day (POD) 1 (118.00±11.16 vs. 62.25±11.16 μg, P=0.001) and POD 2 (59.00±7.41 vs. 18.00±7.41 μg, P<0.001). Similarly, pain at rest was significantly higher in the low-MELD group on POD 1 (39.29±1.01 vs. 35.70±1.01, P=0.019) and POD 2 (28.21±1.01 vs. 22.78±1.00, P=0.001). Conclusions: Among patients with chronic liver disease undergoing living donor liver transplantation, postoperative fentanyl consumption and pain scores were significantly lower in those with a high MELD score compared to patients with a low MELD score.